2016
DOI: 10.1002/chem.201604521
|View full text |Cite
|
Sign up to set email alerts
|

Activation of an Au−Cl Bond by a Pendent SbIII Lewis Acid: Impact on Structure and Catalytic Activity

Abstract: With the objective of identifying new coordination modes of ambiphilic ligands, we have investigated the bidentate Sb/P ligands (o-(Ph P)C H )SbCl (L ) and (o-(Ph P)C H )SbPh (L ). Reaction of these ligands with (tht)AuCl affords the monoligated species L AuCl (1) and L AuCl (2), respectively, in which the antimony centers are only weakly engaged with the coordinated gold atom. Treatment of 1 with PPh induces an intramolecular transfer of a chloride ligand from gold to antimony to form the zwitterionic species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 106 publications
0
27
0
Order By: Relevance
“…Recent efforts in the chemistry of organoantimony(III) have established that derivatives such as I and II readily bind halide anions (Figure ) by donation into the σ* orbital (Figure ) . Based on the same principle, we also found that antimony(III) halides could serve to promote the activation of transition metals either by direct interaction with the metal ( III ) or anion abstraction ( IV ) (Figure ).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Recent efforts in the chemistry of organoantimony(III) have established that derivatives such as I and II readily bind halide anions (Figure ) by donation into the σ* orbital (Figure ) . Based on the same principle, we also found that antimony(III) halides could serve to promote the activation of transition metals either by direct interaction with the metal ( III ) or anion abstraction ( IV ) (Figure ).…”
Section: Figurementioning
confidence: 99%
“…[1] Antimony derivatives,b ecause of their intrinsically higher Lewis acidity, [2] are also drawing considerable attention both in the areas of small-molecule activation and catalysis, [3] as well as in anion complexation. [7] Based on the same principle,w ea lso found that antimony(III) halides could serve to promote the activation of transition metals either by direct interaction with the metal (III) [8] or anion abstraction (IV) [9] (Figure 1). [7] Based on the same principle,w ea lso found that antimony(III) halides could serve to promote the activation of transition metals either by direct interaction with the metal (III) [8] or anion abstraction (IV) [9] (Figure 1).…”
mentioning
confidence: 97%
“…[4] Recent efforts in the chemistry of organoantimony(III) [5] have established that derivatives such as I [6] and II [7] readily bind halide anions ( Figure 1) by donation into the s*orbital (Figure 2). [7] Based on the same principle,w ea lso found that antimony(III) halides could serve to promote the activation of transition metals either by direct interaction with the metal (III) [8] or anion abstraction (IV) [9] (Figure 1).…”
mentioning
confidence: 97%
“…Although a parallel is often drawn with the ubiquitous phosphine ligands, stibines display several atypical traits and can, for example, undergo redox reactions without dissociation of the coordinated metal [5][6][7][8][9][10]. Moreover, while phosphines mostly act as two-electron donor spectator ligands, stibines have been shown to display Lewis acidic properties, even when coordinated to a transition metal [11][12][13][14][15][16][17][18][19][20][21][22]. These Lewis acidic properties manifest in the formation of long contacts between the antimony center of cationic complexes and counteranions as in complex [A] + which was isolated by Reid (Figure 1) [11].…”
Section: Introductionmentioning
confidence: 99%